How can we evaluate the cost-effectiveness of health system strengthening? A typology and illustrations. (January 2019) - Hauck, K.; Morton, A.; Chalkidou, K.; Chi, Y-Ling; Culyer, A.; Levin, C.; Meacock, R.; Over, M.; Thomas, R.; Vassall, A.; Verguet, S.; Smith, P.C.
Abstract: Health interventions often depend on a complex system of human and capital infrastructure that is shared with other interventions, in the form of service delivery platforms, such as healthcare facilities, hospitals, or community services. Most forms of health system strengthening seek to improve the efficiency or effectiveness of such delivery platforms. This paper presents a typology of ways in which health system strengthening can improve the economic efficiency of health services. Three types of health system strengthening are identified and modelled: (1) investment in the efficiency of an existing shared platform that generates positive benefits across a range of existing interventions; (2) relaxing a capacity constraint of an existing shared platform that inhibits the optimization of existing interventions; (3) providing an entirely new shared platform that supports a number of existing or new interventions. Theoretical models are illustrated with examples, and illustrate the importance of considering the portfolio of interventions using a platform, and not just piecemeal individual analysis of those interventions. They show how it is possible to extend principles of conventional cost-effectiveness analysis to identify an optimal balance between investing in health system strengthening and expenditure on specific interventions. The models developed in this paper provide a conceptual framework for evaluating the cost-effectiveness of investments in strengthening healthcare systems and, more broadly, shed light on the role that platforms play in promoting the cost-effectiveness of different interventions. Highlights: Health interventions which rely on joint delivery platforms become interdependent. Such interventions must be evaluated as a portfolio to avoid allocative inefficiency. There are three types of health system strengthening.